Rapid, quantitative, and high-sensitivity detection of anti-phospholipase A2 receptor antibodies using a novel CdSe/ZnS-based fluorescence immunosorbent assay - Chenxi Li (Nature Portfolio, 2021)
Abstract Autoantibodies against M-type phospholipase A2 receptor (PLA2R) serve as specific biomarkers for idiopathic membranous nephropathy (IMN), and its quantification helps monitor disease activity. In this study, we describe a rapid and highly sensitive quantum dots-based immunochromatography assay (QD-ICA) for quantifying PLA2R autoantibodies. Serum samples from 135 biopsy-confirmed patients with nephrotic syndrome were analyzed for PLA2R autoantibodies using the novel QD-ICA as well as commercialized enzyme-linked immunosorbent assay (ELISA). Areas under the receiver operating characteristic curve (AUC-ROC) of QD-ICA were significantly greater than those of ELISA (91.1% [95% CI 85.9–96.3%] and 83.9% [95% CI 76.5–91.2%] respectively; p < 0.01). The detection sensitivity and specificity of QD-ICA (80.9% [95% CI 69.2–89.0%] and 100% [95% CI 93.2–100.0%], respectively) exceeded those of ELISA (72.1% [95% CI 59.7–81.9%] and 98.5% [95% CI 90.9–100.0%], respectively). The optimum cut-off value of QD-ICA was 18.18 relative units (RU)/mL, and the limit of detection was 2.86 RU/mL. The novel QD-ICA outperforms ELISA in detecting PLA2R autoantibodies, with shorter detection time, fewer steps, smaller equipment size, and broader testing application, suggesting its capability to improve IMN diagnosis and monitor patient response to treatment.